Cross-Layer and Cooperative Opportunistic Network Coding in Wireless Ad Hoc Networks - Argyriou, A. (IEEE transactions on vehicular technology, 2010)
In this paper, we present a cross-layer framework for optimizing the performance of opportunistic network coding in wireless multihop networks. The target scenario considers a wireless ad hoc network (WANET) with backlogged nodes and with multiple unicast packet flows. Initially, we focus on modeling the expected network-coded throughput individually for each wireless station as a function of parameters at the lower layers, like the maximum number of link-layer retransmissions and the transmission mode at the physical layer (PHY). Based on this analysis, we develop a network-coding algorithm that opportunistically and locally optimizes the expected information content of individual packet transmissions. To address the problem in a multihop setting, we focus on controlling the air time that is consumed by the resulting transmissions of coded packets. More specifically, we devise a distributed-cooperation algorithm that allows nodes to select the optimal PHY transmission mode by also considering the PHY selection of their neighbors. Nodes use only a partial view of the link contention relationships up to their interference range. Compared with existing works on opportunistic network coding and scheduling in ad hoc networks, our approach can yield significant throughput gains without employing complex link-scheduling algorithms.